2007
DOI: 10.1055/s-2007-993754
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of P-Glycoprotein-Mediated Drug Efflux by Eudesmin from Haplophyllum perforatum and Cytotoxicity Pattern versus Diphyllin, Podophyllotoxin and Etoposide

Abstract: The present study focuses on eudesmin (bicyclic lignan, 0.15 % of dry leaves) and diphyllin (arylnaphthalene lignan, 0.1 % of dry roots), both isolated from H. perforatum Kar. et Kir, a Rutaceae species endemic to Uzbekistan. We first compared their specificity for cancer cells with those of etoposide and podophyllotoxin by screening their cytotoxicity on 3 healthy cell-lines and 7 sensitive or resistant human solid cancer lines. We then tested their capacity to reverse P-glycoprotein-mediated multidrug resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Extracts of stemwood, branchwood, knotwood, and all isolated compounds were evaluated for their cytotoxicity and antioxidant bioassays. In the cytotoxic analysis of eudesmin, it did not give positive cytotoxic activity in SHSY5Y and P3X cells., In comparison to other studies in PC3 (Prostate carcinoma), MCF (Breast carcinoma), PA1 (Ovary carcinoma), DLD1 (Colon carcinoma), or M4Beu (Malignant melanoma) [26], that showed that eudesmin possesses significant antitumor effects on lung cancer A549 (IC50 18.3 uM) via to induction of mitochondria-mediated apoptosis [27], as well as in nasopharyngeal carcinoma cells eudesmin inhibited cell viability and induced apoptosis of NPC cells [28]. However, the cytotoxic activity is not fully understanding, could be suggested that eudesmin is high specific against some particular cancer cell lines; this deserves more in-depth studies and could become a potential cancer-fighting drug.…”
Section: Resultsmentioning
confidence: 80%
“…Extracts of stemwood, branchwood, knotwood, and all isolated compounds were evaluated for their cytotoxicity and antioxidant bioassays. In the cytotoxic analysis of eudesmin, it did not give positive cytotoxic activity in SHSY5Y and P3X cells., In comparison to other studies in PC3 (Prostate carcinoma), MCF (Breast carcinoma), PA1 (Ovary carcinoma), DLD1 (Colon carcinoma), or M4Beu (Malignant melanoma) [26], that showed that eudesmin possesses significant antitumor effects on lung cancer A549 (IC50 18.3 uM) via to induction of mitochondria-mediated apoptosis [27], as well as in nasopharyngeal carcinoma cells eudesmin inhibited cell viability and induced apoptosis of NPC cells [28]. However, the cytotoxic activity is not fully understanding, could be suggested that eudesmin is high specific against some particular cancer cell lines; this deserves more in-depth studies and could become a potential cancer-fighting drug.…”
Section: Resultsmentioning
confidence: 80%
“…Previous reports pointed towards Diphillyn as a substrate of P-glycoprotein (MDR1/P-gp) [ 7 ], thus potentially limiting its therapeutic potential. This prompted us to test their in vitro cytotoxicity on the melanoma cell line SK-Mel-5, reported to be one of the melanoma lineages expressing higher levels of the ABCB1 transcript [ 22 ], both alone and in the presence of non toxic concentrations of verapamil, a known Pgp inhibitor widely used in cancer research [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Later on, the authors claimed that Diphyllin itself have no value as anti-cancer drug, first because its negative cytotoxic index -high tocixicity on both cancer and human primary cells. Modern studies pointed that its anti-proliferative action on cancer cells may involve the cell cycle arrest in the S-phase and inhibition of protein synthesis [ 5 ] but also cytotoxic activity towards human monocytes and skin tissues [ 6 ] and that it is effluxed by P-glycoprotein (P-gp) [ 7 ], thus limiting its therapeutic potential. However, glycosilation may revert the negative cytotoxic index as in the case podophyllotoxin/etoposide.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have reported many therapeutic effects of eudesmin, such as anti-tumor [ 12 , 13 ], anti-fungal [ 14 ], anti-bacterial [ 15 ], and anti-inflammatory [ 16 ] effects, the genomewide analysis in which eudesmin controls multiple sets of genes has not been performed. In this study, we elucidated that eudesmin modulates the expression of PRC2 target genes through comprehensive transcriptomic analysis of our RNA-sequencing data and Enrichr ( Figure 1 A).…”
Section: Introductionmentioning
confidence: 99%